2021
DOI: 10.3390/app11030948
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Cryogenic Facility for Space Debris Analysis

Abstract: This paper has resulted from a continued study of spacecraft material degradation and space debris formation. The design and implementation of a thermal vacuum cycling cryogenic facility for the evaluation of space debris generation at a low Earth orbit (LEO) is presented. The facility used for spacecraft external material evaluation is described, and some of the obtained results are presented. The infrastructure was developed in the framework of a study for the European Space Agency (ESA). The main purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In previous research we have reported a study on generation of space debris in simulated LEO conditions [10,11]. Also, we have reported a first incite on a study on generation of space debris in simulated GEO conditions [12].…”
Section: State Of the Artmentioning
confidence: 99%
“…In previous research we have reported a study on generation of space debris in simulated LEO conditions [10,11]. Also, we have reported a first incite on a study on generation of space debris in simulated GEO conditions [12].…”
Section: State Of the Artmentioning
confidence: 99%
“…The active or passive control of structures at cryogenic temperatures through SMA is a novel and appealing application in severe environments where the temperature might drop extremely low. The space industry may be the main field of application for cryogenic shape memory alloys since they can be used to shield equipment (like satellites) from permanent damage caused by temperature fluctuations brought on by differences in sun irradiation when in orbit [18]. Similarly, these alloys can be used to safeguard cryogenic equipment like infrared detection systems, which are frequently employed in low-temperature environments to increase detection efficiency by reducing background noise interference and dark current detection (these detectors typically operate below 150 K) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent estimates, the number of orbital debris in space amounts to 139 million [4]. Such overpopulation of debris increases the chance of several events that could lead to catastrophic consequences, such as collisions, fragmentations, and uncontrolled reentries in the Earth's atmosphere [4][5][6][7][8][9]. Such a risk forced worldwide space agencies to develop a set of countermeasures to prevent and/or mitigate possible threats.…”
Section: Introductionmentioning
confidence: 99%